On the Historian’s Self-Creation. A Few Notes on the Margins of Wojciech Wrzosek’s Book "Wycinanki" - Mamzer, Henryk (Sensus Historiae, 2023)
The text presented is a commentary on Wycinanki [Cutouts] by Wojciech Wrzosek, a historian and methodologist of historical sciences from Poznan. Wycinanki is a collection of excerpts of statements “cut out” from the texts of various authors such as historians (Robin G. Collingwood, who is also an archaeologist, Michel Foucault, Reinhart Koselleck, Jan Pomorski, representing a decidedly scientistic view of history, Hayden White, Jerzy Topolski), historians of science (Ilona Löwy - author of the Polish School of Philosophy of Medicine), philosophers (Arnold Ayer, Étienne Bonnot de Condillac, Hans Georg Gadamer, Martin Heidegger, Jerzy Kmita, Leszek Kolakowski, José Ortega y Gasset, Anna Palubicka, Willlard Van Orman Quine), as well as anthropologizing historians - (Fernand Braudel, Paul Veyne), ethnologists (Bronislaw Malinowski) or finally writers (Franz Kafka, Milan Kundera, Vladimir Nabokov, Marcel Proust). They express, in fact, the thought of the “cutter” about himself and historical thinking. Thinking about the subject matter that is Wrzosek’s primary area of interest, namely historical thinking, is the main binding agent for the statements presented. It plays the role of a common language in Cutouts, the role of a kind of Koine, which makes possible the reception of the thoughts of representatives of various disciplines mentioned in the book. Wrzosek’s meta-historical reflections on the historical thinking of representatives of various disciplines of the humanities are the reflections aimed at creating a new abstract figure, which is himself - a representative of integrated humanities, which creates in Cutouts - in comparison with the subject language of each fragment – a new metalinguistic quality. This is the AUTOCREATION of the author of Cutouts - the main message of the work, around which the narrative presented in it revolves.